The Role Of Organizational Commitment As A Mediating Variable In Influencing Human Resource Management Strategies And Cross-Generational Conflicts On Employee Performance (PT. Agro Mandiri Logistics) - Yulianti, Devi; Yustiana , Dewi; Uripan, Koen Irianto; Sutoyo; Osijo, Immanuel Ustradi (International Humanity Advance, Business & Sciences, 2026)
This research explores the dynamics of human resources at PT. Agro Mandiri Logistik, Surabaya, by examining the role of organizational commitment as a mediator in the influence of Human Resource Management (HRDM) strategies and cross-generational conflicts on employee performance. With a quantitative approach to support urban logistics efficiency, this study involved 40 cross-generational respondents selected through purposive sampling, with data analysis using Partial Least Squares Structural Equation Modeling (PLS-SEM). The test results prove that the MSDM strategy has a positive and significant direct impact on performance (β=0.607, p=0.000), empirically confirming the validity of the Resource-Based View (RBV) and Ability-Motivation-Opportunity (AMO) theories. In contrast, cross-generational conflicts and organizational commitments did not show a significant influence on performance, and no meaningful mediation role was found across hypothetical pathways. These findings indicate that professionalism in a high-pressure logistics environment is able to mitigate the impact of intergenerational friction without relying on emotional commitment as a key bridge. The study concludes that management should prioritize HRD technical reinforcement such as selective recruitment, adaptive training, and fair rewards as key drivers of productivity.